Estimating PAH sources in harbor sediments using diagnostic ratios. Issue 3 (20th June 2019) - Davis, Emily; Walker, Tony R.; Adams, Michelle; Willis, Rob
Abstract: Polycyclic aromatic hydrocarbons (PAHs) are ubiquitous in the global environment and are subsequently transported into aquatic sediments. As PAHs are formed by various processes, source identification using diagnostic ratios can provide insight to PAH emission sources to distinguish between pyrogenic and petrogenic PAH sources. PAH diagnostic ratios were applied as a forensic source apportionment technique to assess aggregate historical sediment data from 31 small craft harbors (SCHs) across Nova Scotia, Canada. Multiple diagnostic ratios suggest that PAHs present in Nova Scotia SCH sediments are pyrogenic (combustion) in origin, while consistently suggesting that coal‐related PAH sources are potential dominant specific sources. National Institute of Standards and Technology Standard Reference Materials (SRMs) were used as reference for coal tar, urban dust, and diesel exhaust particulates in ratio applications. The SRM for coal tar was most similar to Nova Scotia SCH sediments in multiple ratio applications. Diagnostic ratio results were corroborated by comparing the PAH profile of sediments to source profiles from the literature. Results indicate that Nova Scotia SCH sediments follow global trends by exhibiting a dominant pyrogenic PAH signature, and the specific coal‐related PAH signature of Nova Scotia SCH sediments may be influenced by contamination inputs related to historical industrial coal mining and combustion activities in the province.